(untitled) (Italian Review of Legal History, 2021)
This work aims to present what some Italian jurists at the beginning of 16th century, during a new series of epidemics, thought useful to prevent and preserve from epidemics. Their tracts, in Latin language, were widespread all over Europe since they summarized the experience of many centuries. Their advices were given governments to show how many possibilities were open to deliberate according to the European common law and therefore they are useful tools to judge the enacted local provisions.